Issues of enterprise records management applications : a semantic ontology-based solution perspective / Ahmad Zam Hariro Samsudin, Shah Jahan Miah and Michael McGrath - Samsudin, Ahmad Zam Hariro; Miah, Shah Jahan; McGrath, Michael (Faculty of Information Management, 2013)
Enterprises have increasingly been employed various enterprise record management (ERM) applications for better managing records and contents electronically. However, there are issues in existing ERM applications that impact negatively on users' support, specially to resolve their information query on various records. Throughout a literature review this study identifies both common issues of ERM applications and potential use of semantic ontology, in order to outline a solution foundation. For conducting the investigation the study takes a particular focus on a case of records management in educational institutes. The discussion in this paper helps create a basis for developing a suitable ontology based solution by offering practical benefits to users.